2010
DOI: 10.1111/j.1476-5381.2010.00881.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drug interactions on biotransformation and antiplatelet effect of clopidogrel in vitro

Abstract: The conversion of clopidogrel to its active metabolite, R-130964, is a two-step cytochrome P450 (CYP)-dependent process. The current investigations were performed to characterize in vitro the effects of different CYP inhibitors on the biotransformation and on the antiplatelet effect of clopidogrel. EXPERIMENTAL APPROACHClopidogrel biotransformation was studied using human liver microsomes (HLM) or specific CYPs and platelet aggregation using human platelets activated with ADP. KEY RESULTSExperiments using HLM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 45 publications
2
35
1
1
Order By: Relevance
“…Formation of the oxo intermediate alone is undetectable in the current study. On the other hand, the finding in this study with CYP3A4 and clopidogrel is consistent with other studies, which showed that CYP3A4 could convert clopidogrel to AM and that the carboxylic acid of clopidogrel is inactive in this assay (Zahno et al, 2010). Figure 6 summarizes the findings of this study and compares the results to what is known in the literature concerning oxo-prasugrel conversion.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Formation of the oxo intermediate alone is undetectable in the current study. On the other hand, the finding in this study with CYP3A4 and clopidogrel is consistent with other studies, which showed that CYP3A4 could convert clopidogrel to AM and that the carboxylic acid of clopidogrel is inactive in this assay (Zahno et al, 2010). Figure 6 summarizes the findings of this study and compares the results to what is known in the literature concerning oxo-prasugrel conversion.…”
Section: Discussionsupporting
confidence: 82%
“…SR-26334 is inactive as a P2Y 12 antagonist either directly or after exposure to cytochromes P450. Whether this is because SR-26334 is a poor substrate for cytochrome P450 oxidation or because the ring-opened version of the carboxylic acid is a poor antagonist for the platelet P2Y 12 receptor is unclear, although recent work suggests the former to be the case (Zahno et al, 2010). Metabolic activation of prasugrel, a relatively new choice for antiplatelet therapy, follows a somewhat similar pathway, which involves cleavage of the ester linkage to form the oxo intermediate [2-[2-oxo-6,7-dihydrothieno[3,2-c]pyridin-5(4H)-yl]-1-cyclopropyl-2-(2-fluorophenyl)ethanone] (R-95913) followed by ring opening to the AM, 2-[1-2-cyclopropyl-1-(2-fluorophenyl)-2-oxoethyl]-4-mercapto-3-piperidinylidene acetic acid (R-138727) (Sugidachi et al, 2001;Hasegawa et al, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, simvastatin was shown to be a stronger inhibitor than atorvastatin. 19 This finding can be explained by the difference in the chemical structure of simvastatin and atorvastatin.…”
Section: Clopidogrel and Lipophilic Statins Co-medicationmentioning
confidence: 95%
“…9 Discrepancies in the antiplatelet effect of clopidogrel may be related to differences in the timing of each study, the latter studies being conducted immediately after PCI and with a loading dose of clopidogrel, and an exact time of daily administration of clopidogrel and CYP3A4 metabolized statins. 10 Finally, in a recent subanalysis of the TRITON-TIMI 38 study there was no influence of concomitant use of statins or calcium-channel blocker on clinical outcome in patients treated with either clopidogrel or prasugrel. 11 Thus, the influence of drug-drug interactions on the pharmacodynamic effect of clopidogrel and clinical outcome is still controversial.…”
Section: Article P 679mentioning
confidence: 99%